Pembangunan Destinasi Wisata Berkelanjutan: Satu Pengenalan Konsep dan Praktik Bagi Kepala SMA Se-Kabupaten Aceh Tengah - Ferdi Nazirun Sijabat, Mawardi, Intan Novia Astuti, Nasri Zaman (Bansigom Na Publisher, 2024)
Headmaster of Senior High School in Aceh Tengah Regency has a strategic role in aligning the vision of education with the needs of local tourism development. Their leadership in understanding and supporting the concept of sustainability have a positive impact on achieving sustainable tourism development goals. This article provides insight and inspiration to enhance the role of Headmaster of Senior High School in supporting the development of sustainable tourist destinations, creating a sustainable educational environment, and positively impacting local communities.